PENGARUH GAYA KOMUNIKASI PIMPINAN TERHADAP KINERJA ANGGOTA ORGANISASI MAHASISWA - Salwa Zhafirah; Mohamad Muspawi; Registha Maristin; Syifa Nur Fadillah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the influence of leadership communication style on the performance of members in student organizations. Communication plays an important role in determining the effectiveness of organizational activities, particularly in achieving organizational goals. However, communication problems often occur in student organizations, which can affect members’ performance. This research uses a quantitative approach with a survey method. Data were collected through questionnaires distributed to members of student organizations from several public universities. The data were analyzed using descriptive and inferential statistical techniques. The results show that leadership communication style has a positive relationship with members’ performance. Effective communication by leaders contributes to improving member performance and organizational effectiveness.